2004
DOI: 10.1210/jc.2003-031409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glutamine and Recombinant Human Growth Hormone on Protein Metabolism in Prepubertal Children with Cystic Fibrosis

Abstract: To determine whether recombinant human GH (rhGH) and glutamine (GLN), alone or in combination, have a protein anabolic effect and whether rhGH alters GLN kinetics in cystic fibrosis (CF), nine 9.6 +/- 0.5-yr-old children with CF who were either undernourished (weight/height, <50th percentile) or short (height, <5th percentile) received 2-h infusions of [(13)C]bicarbonate (to assess CO(2) production), followed by 4-h infusions of [(13)C]leucine and [(15)N]GLN, on 4 separate days in the postabsorptive state: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 36 publications
2
41
0
1
Order By: Relevance
“…3, Of the 10 trials, 8 trials compared rhGH to no treatment, [14][15][16][17][23][24][25][26] 1 trial used a placebo control, 3 and 1 trial compared rhGH alone to either glutamine or the combination of glutamine and rhGH. 20 A crossover design was used in 2 trials, 16,20 whereas the others used a parallel study design. 3,14,15,17,[23][24][25][26] Only 1 trial was doubleblinded.…”
Section: Controlled Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…3, Of the 10 trials, 8 trials compared rhGH to no treatment, [14][15][16][17][23][24][25][26] 1 trial used a placebo control, 3 and 1 trial compared rhGH alone to either glutamine or the combination of glutamine and rhGH. 20 A crossover design was used in 2 trials, 16,20 whereas the others used a parallel study design. 3,14,15,17,[23][24][25][26] Only 1 trial was doubleblinded.…”
Section: Controlled Trialsmentioning
confidence: 99%
“…3,14,15,17,[23][24][25][26] Only 1 trial was doubleblinded. 3 Four trials received funding from foundations or government, [14][15][16]26 8 trials received funding from indus-try, 3,14,15,17,20,23,25,26 and a funding source was not reported for 2 of the trials. 24,30 Four of the aforementioned trials received both industry and foundation funding to conduct their studies.…”
Section: Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both animal and human studies have demonstrated that recombinant human growth hormone (rhGH) can enhance protein synthesis, promote tissue recovery, stimulate intestinal epithelial growth, etc. (3)(4)(5). However, the mechanism of the protective effect of rhGH on the intestinal mucosa barrier is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…Sugere-se, inclusive, que a glutamina diminui a atrofia da mucosa intestinal, induzida por diferentes agressões e patologias em modelos animais (WINDMUELLER & SPAETH, 1978) e melhora a função de absorção intestinal (TREMEL et al, 1994). Porém estes efeitos anabólicos, aparentemente, utilizando metodologia mais adequada, não têm sido ratificados em humanos e cães (MARCHINI et al, 1999, DARMAUN et al, 2004. O corpo humano abrange perto de 9 kg de proteína, principalmente na forma de proteína muscular.…”
Section: Abstrac Abstrac Abstrac Abstracunclassified